Comparison of major adverse cardiovascular events between sacubitril-valsartan versus ACEI/ARB therapy in patients with heart failure with reduced ejection fraction. (2nd May 2022) - Tinoco, M; Cardoso, F; Dias, G; Pereira, T; Faria, B; Almeida, F; Leite, S; Lourenco, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Sacubitril-valsartan (S-V) reduced risks of Major Adverse Cardiovascular Events (MACE) for heart failure (HF) versus enalapril in ambulatory patients with HF and reduced ejection fraction (HFrEF) in the PARADIGM-HF trial. However, the comparative MACE of S-V and Angiotensin Converting Enzyme Inhibitors (ACEI)/angiotensin receptor blocker (ARB) in patients treated in routine clinical practice is unclear. Purpose: This study aims to compare the MACE of S-V and ACEI/ARB in HFrEF patients. Methods: Retrospective study of patients with HFrEF observed in a HF clinic between Jan 2018 and Dec 2018, with a follow up at Sept 2021. We defined MACE as composite of death from cardiovascular (CV) causes or hospitalization for HF. One-to-one propensity score matching was used to balance patients on 20 clinical variables. Cox models were used to compare outcomes between treatment groups. Results: A total of 130 HFrEF patients were included, 45 (34, 6%) and 85 (65, 4%) adults filling a prescription for S-V or ACEI/ARB, respectively. Before matching, patients taking S-V had a mean age of 61, 3±10, 8 and were more often men (38; 84%). In the group of patients treated with ACEI/ARB, the mean age was 60, 7±11, 6 and 69 (81%) were male. The most frequent aetiologies for HF were ischemic cardiomyopathy (22; (48, 9%) in S-V group and 37 (43, 5%) in ACEI/ARB group) and dilated cardiomyopathy (21; (46, 7%) in S-V group and (45; 52, 9%) in ACEI/ARB group). The final propensity-matched cohort included 34 pairs taking S-V or ACE/ARB. The median follow-up time was 42 (IQR: 34-61) months. MACE occurred in 11 (32, 4%) patients treated with S-V and in 10 (29, 4%) patients taking ACEI/ARBs. During follow-up, 7 (20, 6%) patients treated with S-V died, compared with 8 (23, 5%) treated with ACEI/ARB. The proportion of CV mortality was 4 (11, 8%) for S-V patients and 3 (9%) for ACEI/ARB patients. HF hospitalization occurred in 9 (26, 5%) patients taking S-V vs 10 (29%) patients taking ACEI/ARBs, of which 6 (17, 6%) and 4 (12%), respectively, were rehospitalised for HF. The same number of patients in both groups (8; 23, 5%) required inotropic support. The median time to the first hospitalization was 17 months (IQR: 7 -35) in the S-V group and 6 months (IQR: 2 -14) in the ACEI/ARB group. There were no statistically significant differences between S-V vs ACEI/ARB in respect to MACE (p=0, 499), all-cause mortality (p=0, 919), CV mortality (p=0, 594) and HF hospitalization (p=0, 207) during follow-up. There was a statistically significant difference between the two groups in respect to the median time to first hospitalization (p=0, 032). Conclusion: In our cohort of patients with HFrEF, sacubitril-valsartan was not associated with lower risks of death and hospitalization compared with ACEI/ARB. Nonetheless, patients treated with sacubitril-valsartan had a median time to first hospitalization higher than the group of patients treated with ACEI/ARB.